Encyclopedia of American poetry. The nineteenth century - Haralson, Eric L.; Hollander, John. (Chicago : Fitzroy Dearborn, 1998)
With contributions from over 100 scholars, this encyclopedia provides essays on the careers, works, and backgrounds of more than 100 nineteenth-century poets. It also provides entries on specialized categories of twentieth-century verse such as hymns, folk ballads, spirituals, Civil War songs, and Native American poetry. Besides presenting essential factual information, each entry amounts to an in-depth critical essay, and includes a bibliography that directs readers to other works by and about a particular poet.
Includes bibliographical references and indexes.
Keywords: American poetry -- 19th century -- Bio-bibliography -- Dictionaries; Poets, American -- 19th century -- Biography -- Dictionaries